THE IMPLEMENTATION OF GOOGLE SITE AS E-LEARNING PLATFORM FOR TEACHING EFL DURING COVID-19 PANDEMIC - Jusriati Jusriati; Nasriandi Nasriandi; Wisnu Kurniadi; Ratna Ratna (English Review: Journal of English Education, 2021)
The aims of this study are to find out whether the implementation of Google Site is effective or not for Teaching EFL and to know the student’s perception toward the implementation of google site in teaching EFL. The subject of the study will be English Students Education at Universitas Muhammadiyah Palopo. The samples of this study will be chosen randomly. The data will be from the EFL Test and interview and all documents use by the lecturer in their teaching and learning process. The EFL test used to measure the students’ improvement after implementing the google sites and the interview used to investigate while the interview done to dig more information on how the students’ perception toward the implementation of google site in teaching EFL. However, through the implementation of the media, it can be said to be effective and attract the attention of students in EFL learning.